The Clark Air Base Nursery School a case study - Almeda, Alice L. (s.n.], 1973)
The Base Nursery School serves the dependents of American military and civilian personnel residing at Clark Air Base. It offers (1) a composite model program approach to provide more individualized curricula fitting the background and experience of the pupils at CAB, and (2) health, safety, nutrition and private transportation services to pupils.